2011
DOI: 10.7824/rbh.v10i3.113
|View full text |Cite
|
Sign up to set email alerts
|

Controle de Ipomoea nil utilizando ponta centrífuga de pulverização em diferentes volumes de aplicação com e sem adjuvante

Abstract: Resumo -A incorporação de ferramentas relacionadas à tecnologia de aplicação de agrotóxicos torna-se inevitável para uma agricultura sustentável. Foi testada a eficiência no controle de Ipomoea nil, em pós-emergência inicial com diuron+hexazinone, em dois volumes de aplicação (20 L ha -1 e 40 L ha -1 ), com ou sem a adição de adjuvantes, utilizando-se pontas de pulverização rotativo e hidráulico, comparativamente. Foram realizados outros dois ensaios para comparar a distribuição volumétrica e o diâmetro das go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
3
0
2
Order By: Relevance
“…The lowest value was obtained in the glyphosate treatment, while treatments glyphosate + vegetable oil and paraquat + tributyl citrate + polydimethylsiloxane had the highest value although without difference with the water (control) ( Table 3). BARBOSA et al (2011) reported that the use of adjuvants, including vegetable oils gave an increase to the volumetric diameter of droplets relative to the absence of adjuvants at spraying liquids, as occurred in this study. There are no defined conclusions about why it happens, especially for models of hydraulic energy.…”
Section: Droplet Sizesupporting
confidence: 70%
“…The lowest value was obtained in the glyphosate treatment, while treatments glyphosate + vegetable oil and paraquat + tributyl citrate + polydimethylsiloxane had the highest value although without difference with the water (control) ( Table 3). BARBOSA et al (2011) reported that the use of adjuvants, including vegetable oils gave an increase to the volumetric diameter of droplets relative to the absence of adjuvants at spraying liquids, as occurred in this study. There are no defined conclusions about why it happens, especially for models of hydraulic energy.…”
Section: Droplet Sizesupporting
confidence: 70%
“…Mombaça com diferentes pontas e volumes de calda (100 e 200 L ha -1 ), concluíram que todos os tratamentos foram eficazes no controle da gramínea, independentemente da ponta e volume utilizados. Da mesma forma, Barbosa et al (2011), ao testarem a eficácia de controle de Ipomoea nil utilizando o herbicida diuron + hexazinone com e sem adjuvante, aplicado com ponta centrífuga de pulverização em diferentes volumes de calda, também constataram que, independentemente do volume de calda utilizado, não houve diferença quanto à eficá-cia de controle da planta daninha estudada, concordando assim com os resultados do presente trabalho. Segundo esses autores, o menor volume com níveis de controle semelhantes diminui os impactos ambientais e proporciona menor custo operacional, pois há maior rendimento na aplicação e menos reabastecimentos do tanque do pulverizador.…”
Section: Methodsunclassified
“…This difference in control can be attributed to the technology chosen for herbicide application. The use of rotating nozzles can provide a better control efficiency by producing uniform-size droplets with low spray solution volumes and reducing the potential risk of drift when compared to hydraulic nozzles (Barbosa et al, 2011).…”
Section: Efficacy Of Controlmentioning
confidence: 99%
“…The use of the rotating nozzle with a volume of 50 L ha -1 provided control similar to that of a CO 2 -pressurized with a hydraulic tip with 200 and 280 L ha -1 (Emerine et al, 2010;Campos et al, 2012). The application of lower spray solution volumes reduces the economic and environmental impacts since volumes above the necessary can cause drift and drainage, with higher risks to the environment (Barbosa et al, 2011).…”
Section: Efficacy Of Controlmentioning
confidence: 99%
See 1 more Smart Citation